Pengaruh Mediapembelajaran Video Iklan Layanan Masyarakat “Edukasi Konsumsi Sayur Dan Buah” Terhadap Keterampilan Berbicara Siswa Tunagrahita - Ratri Wikaningtyas (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2022)
The aim of this research is to explore the impact of using the learning media video public service advertisement "Fruit and Vegetable Consumption Education" on the development of speaking skills of mentally retarded students at SLB N Brebes. This research adopted a quasi-experimental design approach, where there was a control class that underwent conventional learning and an experimental class that implemented learning using the video learning media of public service advertisements "Fruit and Vegetable Consumption Education". Data was collected through oral speaking skills tests before and after treatment. The results of this research show that the public service advertisement video learning media "Fruit and Vegetable Consumption Education" significantly improves students' speaking skills compared to conventional learning. Students who engage in learning using this method achieve greater improvements in indicators such as pronunciation, grammar, vocabulary, fluency, and comprehension. Thus, the learning media of the public service advertisement video "Fruit and Vegetable Consumption Education" has an effect on the speaking skills of mentally retarded students.